The Evolution of Micromechanical Properties for Zr-Based Metallic Glass Induced by Laser Shock Peening - Li, Yansen; Wang, Zhitao; Wei, Yanpeng; Chen, Tianyu; Zhang, Chunfeng; Huan, Yong; Zhang, Kun; Wei, Bingchen (Frontiers in Materials, 2021)
Metallic glasses are considered to be a very promising material due to their highly attractive properties compared to their crystalline counterparts, such as extremely high hardness, high strength and corrosion resistance. However, the poor plastic deformation ability of metallic glasss at ambient temperature greatly hinders their engineering applications. The plastic deformation behavior of metallic glass has aroused much attention in recent years. However, most researches mainly focus their attention on exploring the response characteristics and deformation law of metallic glass by conventional loading methods, such as cold rolling and pre-compression. The evolution of mechanical properties for metallic glass under extreme loading conditions are still not fully understood. In our paper, we aim to shed light on the change of micromechanical properties of metallic glass under extreme loading conditions with ultra-high pressure (~GPa) and ultra-short time (~ ns) is studied, which provides experimental support for deeply understanding the deformation characteristics and mechanisms of metallic glass. The results may also offer a new possible way to improve the plastic ability of metallic glass.